Issues and challenges for the design and implementation of macro-prundential pilocy in Nigeria - Kama, U.; Central Bank of Nigeria, Research Department; Adigun, M.; Adegbe, O.; Central Bank of Nigeria (Abuja, Nigeria Central Bank of Nigeria, 2013)
Highlights the present state of the various discourses about macro-prudential policy and shed more light on the conceptual definitional issues on the subject.
Includes bibliographical references.
oif 22/05/17
Ref.
Keywords: Macroeconomics - Econometric models; Economic stabilization; Monetary policy; Financial crises - Prevention; Finance; Nigeria